A framework for integrating ecosystem services indicators into vulnerability and risk assessments of deltaic social-ecological systems. (15th January 2023) - Peng, Yuting; Welden, Natalie; Renaud, Fabrice G.
Abstract: Due to increasing population pressure and urbanization, as well as global climate change impacts, many coastal river deltas are experiencing increased exposure, vulnerability and risks linked to natural hazards. Mapping the vulnerability and risk profiles of deltas is critical for developing preparedness, mitigation and adaptation policies and strategies. Current vulnerability and risk assessments focus predominantly on social factors, and typically, do not systematically incorporate a social-ecological systems perspective, which can lead to incomplete assessments. We argue that ecosystem services, which link both ecosystem functions and human well-being, can be used to better characterize the mutual dependencies between society and the environment within risk assessment frameworks. Thus, building on existing vulnerability and risk assessment frameworks, we propose a revised indicator-based framework for social-ecological systems of coastal delta environments, supported by a list of ecosystem service indicators that were identified using a systematic literature review. This improved framework is an effective tool to address the vulnerability and risk in coastal deltas, enabling the assessment of multi-hazard risks to social-ecological systems within and across coastal deltas and allows more targeted development of management measures and policies aimed at reducing risks from natural hazards. Highlights: Assessing risks from natural hazards is crucial for coastal river deltas. There is an imbalance in the representation of social and ecological systems in risk assessments. A new risk assessment framework in proposed where ecosystem services are systematically considered. A comprehensive indicator library is provided for risk assessments.